Analisis Perspektif Guru dalam Pembelajaran IPA Pada Kurikulum Merdeka Belajar di Sekolah Dasar Negeri 2 Ranjeng Kabupaten Indramayu Provinsi Jawa Barat - Yasin, Yasin; Setiyoko, Didik Tri; Nisa, Hani Uswatun; Yulianti, Novi; Muamar, Muamar (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to determine educational problems at the Ranjeng 2 Elementary School, Indramayu Regency which has implemented the Merdeka Curriculum. The method that researchers used was the observation method, as well as interviews for teachers and questionnaires for students. This research uses data collection that utilizes interview techniques and documentation techniques, and analysis is carried out using data triangulation and method triangulation. Interviews were conducted with several sources who were considered to be directly affected by the changes to the independent curriculum that were being implemented in schools and were only specifically for class VI students. The conclusion from the results of this research is that changes in the curriculum have caused some confusion for the majority of teachers who teach science learning in class VI with an independent curriculum. The lack of direct guidance from the government regarding the implementation of the independent curriculum means that teachers can only imitate driving schools that have implemented the independent curriculum with direct direction from the government. The number of educators to foster the implementation of the independent curriculum in class VI is also considered insufficient so that many teachers feel overwhelmed, and even have to sacrifice mentoring hours for teaching schedules in other classes, where the existing schedules conflict. Teachers also feel that the implementation of project learning has several positive and negative impacts on students. The positive impact is that students have abilities that are honed by technological advances, while the negative is that students will get bored because project learning is carried out consecutively for two weeks without any material learning.